2018
DOI: 10.1016/j.ijso.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sub-hypnotic dose of propofol on prevention of postoperative nausea and vomiting as part of multimodal antiemetic in patients undergoing open abdominal surgery: A prospective cohort study, Gondar University Hospital, Northwest Ethiopia, 2016

Abstract: Background: Postoperative nausea and vomiting (PONV) is one of the most common and unpleasant symptoms affecting patients undergoing abdominal surgery under general anaesthesia. It is also associated with complications such as gastric aspiration, bleeding, dehydration, wound dehiscence and delayed hospital discharge. Objective: The aim of this study was to assess the effect of a sub hypnotic dose of propofol on the occurrence and severity of PONV after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Statistically significant results were obtained at the 12th to 24th hour time period ( p < 0.044). Studies suggest that effective concentration of propofol is better maintained in IV infusion rather than bolus dosing to prevent PONV [ 27 , 28 ]. The antiemetic effect of propofol is attributed to modulation of subcortical pathways to inhibit nausea or its direct depressant action on the vomiting center [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant results were obtained at the 12th to 24th hour time period ( p < 0.044). Studies suggest that effective concentration of propofol is better maintained in IV infusion rather than bolus dosing to prevent PONV [ 27 , 28 ]. The antiemetic effect of propofol is attributed to modulation of subcortical pathways to inhibit nausea or its direct depressant action on the vomiting center [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients anesthetized with Propofol as opposed to Sevoflurane, the incidence of PONV during the first 24 postoperative hours was significantly lower, according to a study by Shinn et al [28]. According to Yirmer et al, numerous studies have also demonstrated that 30 mg of intravenous propofol can reduce the incidence of PONV without causing any noticeable side effects [15] (Table 1). In addition, Celik et al found that 1 mg/kg/h of infusion of propofol is equally effective as dexamethasone for preventing PONV in patients undergoing laparoscopic cholecystectomy during the first 24 hours [29].…”
Section: Antiemetic Effect Of Propofolmentioning
confidence: 96%
“…Rosillo-Menesesa et al demonstrated that propofol primarily acts on GABA receptors by increasing chloride ion conduction. Although the precise mechanism by which Propofol acts as an antiemetic remains elusive, it has been hypothesized that its antiemetic effects may be a result of the 5-HT3 receptor antagonist in the postrema region by gamma-aminobutyric acid (GABA) [15]. This makes it potentially effective for treating nausea and vomiting in the context of palliative care [10].…”
Section: Antiemetic Effect Of Propofolmentioning
confidence: 99%